2021
DOI: 10.1080/19490976.2021.1884516
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of toxin B and binary toxin in Clostridioides difficile infection

Abstract: To study the association between detection of the Clostridioides difficile gene encoding the binary toxin (CDT) and direct detection of toxinB (TcdB) from feces with the appearance of serious disease, complications, or recurrence in a prospective series of cases. A total of 220 confirmed cases were included, using a two-step algorithm: an initial study to detect the enzyme, glutamate dehydrogenase (GDH), followed, in cases of positivity, by detection of the tcdB. tcdB-positive patients were investigated for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…The search for prognostic factors for sCDI yielded 1242 references; 126 studies were assessed in more detail and 76 were included for analysis [20,24,25,29,; twelve more studies retrieved from cross-references were also included [111][112][113][114][115][116][117][118][119][120][121][122] resulting in 88 studies for final analysis (Figure 1). The search for prognostic factors for rCDI yielded 1104 references; 105 studies were assessed in more detail and 36 were included for analysis [9, 10, 12-15, 103, 110, 123-150] as were seven studies from cross-references.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for prognostic factors for sCDI yielded 1242 references; 126 studies were assessed in more detail and 76 were included for analysis [20,24,25,29,; twelve more studies retrieved from cross-references were also included [111][112][113][114][115][116][117][118][119][120][121][122] resulting in 88 studies for final analysis (Figure 1). The search for prognostic factors for rCDI yielded 1104 references; 105 studies were assessed in more detail and 36 were included for analysis [9, 10, 12-15, 103, 110, 123-150] as were seven studies from cross-references.)…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, seven studies assessed C. difficile binary toxin as risk factor for sCDI [47,83,92,95,118,120,122]. Of these, three identified C. difficile binary toxin as a risk factor for sCDI in univariate analysis, and only 1/1 study in multivariate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The search for prognostic factors for sCDI yielded 1242 references; 126 studies were assessed in more detail and 76 were included for analysis (20,24,25,29,; twelve more studies retrieved from cross-references were also included (110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121) resulting in 88 studies for final analysis (Figure 2). The search for prognostic factors for rCDI yielded 1104 references; 105 studies were assessed in more detail and 36 were included for analysis (9, 10, 12-15, 102, 109, 122-149) as were seven studies from cross-references.)…”
Section: Resultsmentioning
confidence: 99%
“…One study found that NAP1/027 was more prevalent in patients with mild disease compared to patients with sCDI (44). Furthermore, seven studies assessed C. difficile binary toxin as risk factor for sCDI (45,82,91,94,117,119,121). Of these, three identified C. difficile binary toxin as a risk factor for sCDI in univariate analysis, and only 1/1 study in multivariate analysis.…”
Section: Figure 2 Flow Diagram Of the Selection Process Of Studies On Prognostic Factors For Severe/recurrent CDImentioning
confidence: 99%
“…Although the large Rho/Ras-glycosylating toxins TcdA and TcdB are regarded as the main virulence factors of C. difficile, increasing numbers of strains have been identified that additionally release CDT [1,9,45,46]. The role of CDT as a virulence factor is still under debate.…”
Section: Discussionmentioning
confidence: 99%